"Impact of the Accounting Conservatism on the Efficiency of Investment in Jordanian Public Shareholding Companies" - El-Dalabeeh, Abdel Rahman; Al-Khaza’leh, Qutaiba (The Arab Journal of Administration, 2022)
The study examined the effect of accounting conservatism on the efficiency of investment in pharmaceutical companies and public sector health companies listed on the Amman Stock Exchange. This study was conducted on two subsectors, the pharmaceutical industry consisting of four companies and the health services sector, which is also composed of four companies during the period (2010-2017). To achieve the objectives of the study, the researcher used the descriptive analytical method .The study also used the book value equity to the market value of the equity model to measure the accounting conservatism. To measure the efficiency of the investment, two measures were used: the deviation from the expected investment and the Market value per share to earnings per share model to study the semi-annual financial reports of the sample companies for the period 2010-2017. The study also used the statistical program (Eviews) to test the hypotheses of the study and used the following statistical methods (Simple regression, regression of fixed effects, regression of random effects, aggregate regression, multiple regression, correlation coefficients by Pearson test, Haussmann test). The study concluded that the accounting conservatism effects on the efficiency of the investment measured by the model of market value to return negatively. It also concluded that the accounting conservatism affects the efficiency of the investment measured by the deviation model from the expected investment positively. The study also found that three companies from the sample of the study apply the policy of accounting conservatism. The study recommended not abandoning the application of conservative accounting policies with the moderation in their application, as their application makes the accounting information more appropriate to decision-making, in addition to the excessive application may harm the company to believe that the shareholder invests his money in a less successful facility.